Psychopathological investigation of the personality of "psychic mediums": Clinical evidence - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2023)
Background: In popular culture, the medium is a subject of seemingly controversial psychic abilities, as he or she seems to be able to communicate telepathically and physically with the various spirit entities present on the astral plane, i.e., a plane parallel to the physical one that can interact with it. In the literature, such assumptions rise to mere speculation, the result of superstition and personal beliefs, using the abilities of mental manipulation; however, some research has challenged these beliefs. Objectives: To demonstrate whether the personality profile of the psychic mediums analyzed exhibits pathological personality traits and whether such is sufficient to confirm a clinical diagnosis. Materials and methods: Clinical interview, based on narrative-anamnestic and documentary evidence, and battery of psychometric tests.  Results: The totality of the clinical group (CG) is found to be pathological, with at least 5 dysfunctional traits, and a corollary of secondary traits reinforcing the primary condition; the pathological differential from the control group (Cg) is +70.7%. At the individual sexual matrix questionnaires, just over 1/4 of the CG show a dysfunctional tendency to sexual behavior with a differential from the Cg of +42.8%. Slightly more than one-fifth of the CG also exhibit affective dependence, with a pathological differential with the Cg of +17%, while the CG sample concerning ego defense mechanisms exhibits the pathological totality of the sample, with a differential for the Cg of +45.7%. Conclusion: This research confirms the psychopathological nature of the personality profiles of mediums, with a higher prevalence of delusional, dissociative, and narcissistic disorders of the overt type, although these results do not prove the fraudulent nature of the mediumistic activity boasted by the subjects, and therefore what has been obtained should be read more generally, subjecting psychic mediums (in mediumistic activity) to technical instrumentation (electroencephalogram, functional magnetic resonance imaging and signal potential and audio-video) in the future to verify the outcomes.